1, 25(OH)2D3 alleviates DSS-induced ulcerative colitis via inhibiting NLRP3 inflammasome activation. Issue 1 (1st April 2020) - Cao, Run; Ma, Yuting; Li, Shaowei; Shen, Donghai; Yang, Shuang; Wang, Xuance; Cao, Yue; Wang, Zhizeng; Wei, Yinxiang; Li, Shulian; Liu, Guangchao; Zhang, Hailong; et al.
Abstract: 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3, VitD3) is the major active ingredient of vitamin D and has anti-inflammatory activity; however, the mechanism for this remains poorly understood. In this study, we found that VitD3 was able to abolish NOD-like receptor protein 3 (NLRP3) inflammasome activation and subsequently inhibit caspase-1 activation and IL-1β secretion via the vitamin D receptor (VDR). Furthermore, VitD3 specifically prevented NLRP3-mediated apoptosis-associated speck-like protein with a caspase-recruitment domain (ASC) oligomerization. In additional to this, NLRP3 binding to NIMA-related kinase 7 (NEK7) was also inhibited. Notably, VitD3 inhibited autophagy, leading to the inhibition of the NLRP3 inflammasome. Uncoupling protein 2-reactive oxygen species signaling may be involved in inflammasome suppression by VitD3. Importantly, VitD3 had both preventive and therapeutic effects on mouse model of ulcerative colitis, via inhibition of NLRP3 inflammasome activation. Our results reveal a mechanism through which VitD3 represses inflammation and prevents the relevant diseases, and suggest a potential clinical use of VitD3 in autoimmune syndromes or other NLRP3 inflammasome-driven inflammatory diseases.